Determined by reasons: a competence account of acting for a normative reason - Mantel, Susanne (Routledge Studies in Ethics and Moral Theory, 2018)
Cover -- Title -- Copyright -- Dedication -- Contents -- List of Figures -- Acknowledgments -- 1 Introduction -- Part 1 Acting for a Normative Reason -- 2 The Causal Approach and the Role of Dispositions -- 3 The Normative Competence Account -- 4 Two Ways of Acting for a Normative Reason -- 5 Conclusion of Part 1 -- Part 2 Squaring Normative Reasons With Motivating Reasons -- 6 The Identity Thesis -- 7 Worldly Reasons in the Deliberative Realm -- 8 Worldly Reasons in the Explanatory Realm -- 9 Worldly Reasons and the Psychological Tradition -- 10 Conclusion of Part 2 and General Reflections -- References -- Appendix -- Index